A controllable hierarchical catalytic structure Pd, cerium oxide, silicon dioxide composite material and its preparation method and application

By preparing Pd/CeO2/SiO2 materials with controllable hierarchical catalytic structure, the problems of harsh reaction conditions and cumbersome catalyst preparation in the hydrogenation conversion of furfural are solved, and efficient cyclopentanone generation and catalyst recycling are achieved, and there is good industrial application prospect.

CN116060000BActive Publication Date: 2025-03-04YANGZHOU UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202310148951.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-22
Publication Date
2025-03-04
Estimated Expiration
2043-02-22

AI Technical Summary

Technical Problem

The reaction conditions of the existing catalysts during the hydroconversion of furfural to cyclopentanone are harsh, and the catalyst preparation is cumbersome, which is not conducive to industrialization. Moreover, the silica-supported Pd catalyst has poor selectivity for cyclopentanone, and the cerium-supported Pd catalyst has an obstacle to the conversion of furfurfurfural alcohol to cyclopentanone.

Method used

A multi-step deposition strategy was used to prepare Pd/CeO2/SiO2 material with a controllable hierarchical catalytic structure. The Pd species were supported by oxygen-rich cerium oxide as a support, and it was dispersed on the surface of acidic silica with a high specific surface area, and prepared by high temperature calcination and reduction.

Benefits of technology

It significantly improves the conversion rate of furfural and cyclopentanone selectivity, has green and efficient reactions, can be separated and recycled, and has simple preparation method, low synthesis cost, and has good industrial application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116060000B_ABST
    Figure CN116060000B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of material preparation, and discloses a preparation method and application of a composite material of Pd, cerium oxide and silicon dioxide with a controllable hierarchical catalytic structure. Cerium oxide rich in oxygen vacancies is used as a carrier, and Pd species are loaded by impregnation, and then dispersed on the surface of acidic silicon dioxide with a high specific surface area. Finally, a Pd / CeO2 / SiO2 material with a controllable hierarchical catalytic structure is prepared by high-temperature calcination and reduction, and is used to catalyze the hydrogenation conversion reaction of furfural. The preparation method of the present invention is simple, green and environmentally friendly, highly active, stable, cheap and easy to obtain, and can efficiently catalyze the hydrogenation conversion of furfural, and has good industrial application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of material preparation, and particularly relates to a controllable hierarchical catalytic structure of Pd, cerium oxide, silicon dioxide material (Pd / CeO2 / SiO2) and a preparation method thereof and application in furfural hydrogenation conversion. Background Art

[0002] Furfural is a typical biomass platform compound that can be prepared on a large scale through the hydrolysis process of lignocellulose. Since furfural contains furan rings and carbonyl functional groups in its molecular structure, it provides the possibility of its transformation into a variety of high value-added chemicals; at the same time, the process is green and low-carbon from biomass, which is in line with the national environmental and energy strategy. Cyclopentanone is an important multifunctional chemical widely used in the food and chemical industries. At present, the adipic acid cracking process for the industrial production of cyclopentanone has problems such as high pollution and high energy consumption. The conversion of furfural into cyclopentanone through catalytic hydrogenation provides a new path to solve the above problems.

[0003] Lee et al. studied the catalytic performance of furfural hydrogenation by Pd supported on different oxide carriers and found that Pd / Co3O4 had the highest activity, with the main product being 2-methylfuran ( Catalysis Today 2021, 365, 291-300). Gao et al. used pyrochlore / alumina composite to load Pd, which showed excellent catalytic performance for furfural hydrogenation, with a cyclopentanone yield of up to 98% ( Applied Catalysis A: General 2021, 612 , 117985). Li et al. used MIL-MOFs to load precious metals for catalytic furfural hydrogenation and found that Fe-MIL-100 and Fe-MIL-101 as carriers could improve the selectivity of cyclopentanone ( Applied Catalysis A: General 2019, 575 , 152-158). In addition to precious metal catalysts, non-precious metal Co-based, Ni-based, and Cu-based materials have also been used to catalyze the hydrogenation of furfural to produce cyclopentanone ( Renewable Energy 2022, 195 , 957-971; Catalysis Letters 2022, doi.org / 10.1007 / s10562-022-04097-x; Molecular Catalysis 2021, 510 , 111697). Zhou et al. prepared a Cu-Mg-Al composite oxide for catalytic furfural hydrogenation. When the Cu / Mg atomic ratio was 0.2, the furfural conversion rate reached 99% and the cyclopentanone selectivity reached 95% ( Journal of Energy Chemistry 2014, 23, 91-96). Although some catalysts reported in the literature show high performance for the hydrogenation of furfural to cyclopentanone, the reaction conditions are relatively harsh and the catalyst preparation process is cumbersome, which is not conducive to industrialization.

[0004] Mesoporous silica has a high specific surface area and stability and is widely used as a catalyst carrier. Silica-supported Pd catalysts show excellent activity for furfural hydrogenation, but poor selectivity for the target product cyclopentanone ( Catalysts 2020, 10 , 837). Cerium oxide has a significant promoting effect on many oxidation and hydrogenation reactions due to its tunable chemical valence and the presence of surface oxygen vacancies. Cerium oxide-supported Pd catalysts have high selectivity for the carbonyl hydrogenation of furfural, but the lack of acidic sites on their surface hinders the conversion of furfuryl alcohol to cyclopentanone ( Fuel 2022, 311 , 122584). In view of the opposite catalytic hydrogenation behaviors of silicon dioxide and cerium oxide loaded Pd, the present invention provides a Pd / CeO2 / SiO2 material with a controllable hierarchical catalytic structure, which organically combines the advantages of the two and promotes the conversion of furfural hydrogenation to cyclopentanone. Summary of the invention

[0005] To solve the above problems, the purpose of the present invention is to provide a method for preparing a composite material of Pd, cerium oxide and silicon dioxide with a controllable hierarchical catalytic structure and its application in the hydrogenation conversion of furfural, which can significantly improve the furfural conversion rate and cyclopentanone selectivity. The reaction is green and efficient, and the catalyst can be separated and recycled.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] A controllable hierarchical catalytic structure Pd, cerium oxide, silicon dioxide composite material, wherein the controllable hierarchical catalytic structure Pd, cerium oxide, silicon dioxide composite material is Pd / CeO2 / SiO2; the Pd loading in the composite material is 0.4-2.0 wt.%; and the mass ratio of CeO2 to SiO2 is 0.05-0.20.

[0008] The present invention also provides a method for preparing the above-mentioned controllable hierarchical catalytic structure Pd, cerium oxide, silicon dioxide composite material, the method comprising the following steps:

[0009] Dissolve hexadecyltrimethylammonium bromide, tetraethyl orthosilicate and aluminum chloride in an ethanol aqueous solution, adjust the solution pH to alkaline, stir vigorously, wash and dry the precipitate, and then calcine in air to obtain acidic silica with high specific surface area; dissolve palladium chloride in a hydrochloric acid aqueous solution, then drop the palladium chloride solution onto solid cerium hydroxide, and stir until the water is completely evaporated; then, disperse it and the acidic silica with high specific surface area in ethanol, stir until the ethanol is completely evaporated, and obtain a Pd / CeO2 / SiO2 precursor; calcine the Pd / CeO2 / SiO2 precursor in air, and obtain Pd / CeO2 / SiO2 after hydrogen reduction.

[0010] Furthermore, in an air atmosphere, the Pd / CeO2 / SiO2 precursor is calcined for 3-5 hours at a heating rate of 1.5°C / min.

[0011] Furthermore, the reduction temperature of the Pd / CeO2 / SiO2 precursor is in the range of 150-200°C and the time is 1-3 hours.

[0012] Furthermore, the preparation method of the cerium hydroxide solid is: dissolving cerium nitrate in water, adding NaOH solution under vigorous stirring to adjust the pH value to 10.5; and obtaining the cerium hydroxide solid after filtering and washing with water.

[0013] Furthermore, the pH value of the solution is adjusted to be alkaline by using aqueous ammonia to adjust the pH value of the solution to 11.0.

[0014] Furthermore, the calcination temperature of the Pd / CeO2 / SiO2 precursor in air is 450°C.

[0015] Furthermore, the precipitate is washed and dried, and then calcined at 550° C. in air to obtain acidic silica with a high specific surface area.

[0016] Furthermore, the method comprises the following steps:

[0017] 1.0 g hexadecyltrimethylammonium bromide, 4.7 g ethyl orthosilicate and a certain amount of aluminum chloride were weighed and dissolved in 500 mL of a solution with a volume ratio of 4:1 of ethanol to water, and then 20 mL of ammonia water was added to adjust the pH value of the solution to 11.0; the solution was stirred vigorously at 80 °C for 2 hours, and the precipitate was filtered, washed with water / ethanol three times, and dried, and then calcined at 550 °C in air to obtain acidic silica with high specific surface area. The specific surface area of ​​acidic silica with high specific surface area is as high as 1253 m 2 / g.

[0018] A certain amount of cerium nitrate was dissolved in 5.0 mL of water. Under vigorous stirring, 2.0 mol / L of NaOH solution was added to adjust the pH value to 10.5. After filtering and washing with water, solid cerium hydroxide was obtained. The specific surface area of ​​the solid cerium hydroxide was 97 m 2 / g; a certain amount of palladium chloride is dissolved in 1.0 mL of hydrochloric acid aqueous solution with a pH value of 3.0, and then the palladium chloride solution is dropped onto the cerium hydroxide solid, and stirred at 100 °C until the water is completely evaporated to obtain Pd / Ce(OH)4 solid; subsequently, the Pd / Ce(OH)4 solid and acidic silica with a high specific surface area are dispersed in 3.0 mL of ethanol, and the mass ratio of Pd / Ce(OH)4 to acidic silica with a high specific surface area is 0.07-0.25:1; stirred at 80 °C until the ethanol is completely evaporated; finally, calcined at 450 °C in air, and Pd / CeO2 / SiO2 is obtained after hydrogen reduction.

[0019] Furthermore, the mass ratio of aluminum chloride to tetraethyl orthosilicate in the mixed solution is in the range of 0.01-0.15, thereby controlling the Si / Al atomic ratio in Pd / CeO2 / SiO2 to be 20-30.

[0020] Furthermore, the Si / Al atomic ratio is 28.

[0021] Furthermore, the mass ratio of cerium nitrate to silicon dioxide is in the range of 0.10-0.40, thereby controlling the mass ratio of CeO2 to SiO2 in Pd / CeO2 / SiO2 to be in the range of 0.05-0.20.

[0022] Furthermore, the mass ratio of CeO2 to SiO2 is 0.10.

[0023] Furthermore, the mass ratio of palladium chloride to cerium nitrate is in the range of 0.04-0.20, thereby controlling the Pd loading in Pd / CeO2 / SiO2 to be in the range of 0.4-2.0 wt.%.

[0024] Furthermore, the Pd loading was 1.0 wt.%.

[0025] Furthermore, in air atmosphere, the Pd / CeO2 / SiO2 precursor was calcined for 3-5 hours at a heating rate of 1.5 °C / min.

[0026] Furthermore, the reduction temperature of the Pd / CeO2 / SiO2 precursor ranges from 50 to 200°C and the reduction time ranges from 1 to 3 hours.

[0027] Furthermore, the reduction temperature and time of Pd / CeO2 / SiO2 precursor were 150 °C and 1 h, respectively.

[0028] Furthermore, the Pd loading in Pd / CeO2 / SiO2 was 1.0 wt.%.

[0029] The present invention also provides a composite material of Pd, cerium oxide and silicon dioxide having a controllable hierarchical catalytic structure prepared by the above method.

[0030] The present invention also provides the use of the controllable hierarchical catalytic structure Pd, cerium oxide, silicon dioxide composite material prepared by the above method in the preparation of cyclopentanone by furfural hydrogenation conversion.

[0031] Furthermore, the reaction time of furfural hydrogenation conversion is 0.5-5 hours, and the reaction temperature is 130-150°C. Beneficial Effects

[0032] (1) The present invention adopts a multi-step deposition strategy, using oxygen-vacancy-rich cerium oxide as a carrier, loading Pd species by impregnation, and then dispersing it on the surface of acidic silica with a high specific surface area. Finally, the Pd / CeO2 / SiO2 material with a controllable hierarchical catalytic structure is prepared by high-temperature calcination and reduction. First, the oxygen-deficient cerium oxide surface is conducive to the vertical adsorption of furfural through carbonyl groups, activating carbonyl groups, thereby improving the selectivity of furfuryl alcohol; at the same time, the acidic sites on the silica surface can accelerate the furan ring hydrogenation reforming of furfuryl alcohol catalyzed by acid, and promote the formation of cyclopentanone; in addition, by separating Pd from the silica surface, the furan ring hydrogenation of furfural is inhibited, and the selectivity of tetrahydrofurfuryl alcohol is greatly reduced; finally, by changing the cerium oxide content in the Pd / CeO2 / SiO2 material, the main product of furfural hydrogenation can be regulated from tetrahydrofurfuryl alcohol to furfuryl alcohol and cyclopentanone.

[0033] (2) The Pd / CeO2 / SiO2 material of the present invention is used to catalyze the hydrogenation conversion of furfural, which can significantly improve the furfural conversion rate and cyclopentanone selectivity. The reaction is green and efficient, and the catalyst can be separated and recycled.

[0034] (3) The preparation method of the Pd / CeO2 / SiO2 material of the present invention is simple, the synthesis cost is low, and the process is simple, and it has good industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 TEM image and EDS element distribution map of the Pd / CeO2 / SiO2 material prepared in Example 1 of the present invention;

[0036] Figure 2 The XRD pattern of the Pd / CeO2 / SiO2 material prepared in Example 1 of the present invention;

[0037] Figure 3 The Raman graph of the Pd / CeO2 / SiO2 material prepared in Example 1 of the present invention;

[0038] Figure 4 XPS spectra of Pd3d and Ce3d of the Pd / CeO2 / SiO2 material prepared in Example 1 of the present invention; a is Pd3d, b is Ce3d;

[0039] Figure 5 XRD patterns of Pd / CeO2 / SiO2 materials with different CeO2 / SiO2 mass ratios prepared in Example 2 of the present invention;

[0040] Figure 6 The Raman graphs of Pd / CeO2 / SiO2 materials with different CeO2 / SiO2 mass ratios prepared in Example 2 of the present invention;

[0041] Figure 7 XPS spectra of Pd3d and Ce3d of Pd / CeO2 / SiO2 materials with different CeO2 / SiO2 mass ratios prepared in Example 2 of the present invention; a is Pd3d, b is Ce3d;

[0042] Figure 8 The conversion rate and product distribution diagram of the hydrogenation of furfural catalyzed by Pd / CeO2 / SiO2 materials with different CeO2 / SiO2 mass ratios prepared in Examples 1 and 2 of the present invention;

[0043] Fig. 9 The conversion rate and product distribution of the hydrogenation of furfural catalyzed by the Pd / CeO2 / SiO2 material prepared in Example 1 of the present invention vary with the reaction temperature and time; a is temperature, b is time;

[0044] Fig.10 The conversion rate and product distribution diagram of the catalytic hydrogenation of furfural by 5 cycles of the Pd / CeO2 / SiO2 material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0045] The technical solution of the present invention is described in detail below in conjunction with the accompanying drawings and embodiments. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and cannot be used to limit the protection scope of the present invention.

[0046] When the catalyst of the present invention is used in furfural hydrogenation conversion, excellent catalytic reaction performance can be achieved, including higher furfural conversion rate and cyclopentanone selectivity.

[0047] The preparation method of the Pd / CeO2 / SiO2 composite material with a controllable hierarchical catalytic structure includes the following steps:

[0048] Step (1), weighing 1.0 g of hexadecyltrimethylammonium bromide, 4.7 g of tetraethyl orthosilicate and a certain amount of aluminum chloride, dissolving them in 500 mL of a solution of ethanol and water in a volume ratio of 4:1, then adding 20 mL of ammonia water to adjust the pH value of the solution to 11.0; vigorously stirring at 80 ° C for 2 hours, filtering the precipitate, washing it with water / ethanol three times and drying it, and then calcining it at 550 ° C in air to obtain acidic silica with a high specific surface area.

[0049] Step (2), dissolving a certain amount of cerium nitrate in 5.0 mL of water, adding 2.0 mol / L NaOH solution under vigorous stirring to adjust the pH value to 10.5; filtering and washing to obtain solid cerium hydroxide; dissolving a certain amount of palladium chloride in 1.0 mL of hydrochloric acid aqueous solution with a pH value of 3.0, then dropping the palladium chloride solution onto the solid cerium hydroxide, stirring at 100 ° C until the water is completely evaporated; then, dispersing it and a certain amount of high specific surface area acidic silica obtained in step (1) in 3.0 mL of ethanol, stirring at 80 ° C until the ethanol is completely evaporated; finally, calcining at 450 ° C in air, and reducing with hydrogen to obtain Pd / CeO2 / SiO2.

[0050] Furthermore, in step (2) of the present invention, the Si / Al atomic ratio in the Pd / CeO2 / SiO2 material is 20-30.

[0051] Furthermore, in step (2) of the present invention, the mass ratio of CeO2 to SiO2 in the Pd / CeO2 / SiO2 material is between 0.05 and 0.20, and the loading amount of Pd is between 0.4 wt.% and 2.0 wt.%.

[0052] Furthermore, the mass ratio of CeO2 to SiO2 is preferably 0.1, and the Pd loading is preferably 1.0 wt.%.

[0053] Preferably, in step (2), the reduction temperature is 150°C and the time is 1 hour.

[0054] Preferably, the reaction time is 3 hours and the reaction temperature is 150 °C. Example 1

[0055] 1.0 g of hexadecyltrimethylammonium bromide, 4.7 g of tetraethyl orthosilicate and 0.07 g of aluminum chloride were weighed and dissolved in 500 mL of a solution with a volume ratio of 4:1 of ethanol to water, and then 20 mL of ammonia water was added to adjust the pH value of the solution to 11.0; the solution was vigorously stirred at 80 °C for 2 hours, and the precipitate was filtered, washed with water / ethanol three times and dried, and then calcined at 550 °C in air to obtain acidic silica with high specific surface area; 0.091 g of cerium nitrate was dissolved in 5.0 mL of water, and 2.0 mol / L of NaOH solution was added under vigorous stirring to adjust the pH value to 10.5; solid cerium hydroxide was obtained after filtration and washing; 0.0084 g of palladium chloride was dissolved in 1.0 mL of hydrochloric acid aqueous solution with a pH value of 3.0, and then the palladium chloride solution was added dropwise to the cerium hydroxide solid, and stirred at 100 °C until the water was completely evaporated; then, it and 0.47 g of acidic silica with high specific surface area were dispersed in 3.0 mL of ethanol and stirred at 80 °C until the ethanol was completely evaporated; finally, it was calcined at 450 °C in air and reduced with hydrogen at 150 °C for 1 hour to obtain Pd / CeO2 / SiO2.

[0056] The results of element determination showed that the mass ratio of CeO2 / SiO2 in the prepared Pd / CeO2 / SiO2 material was 0.1 and the Pd loading was 1.0 wt.%. Figure 1 The TEM image and EDS element distribution map of the prepared Pd / CeO2 / SiO2 material confirm that Pd is completely distributed on the cerium oxide, while the cerium oxide is dispersed on the surface of the silicon dioxide. Figure 2 The XRD pattern of the prepared Pd / CeO2 / SiO2 material shows that cerium oxide is loaded on silica, and the absence of Pd diffraction peak indicates that it is highly dispersed. Figure 3 The Raman spectrum of the prepared Pd / CeO2 / SiO2 material is located at 590 cm -1 The peak at 667 cm-1 indicates the presence of oxygen vacancies in cerium oxide. -1 The peak at confirms that Pd interacts with the cerium oxide surface to form a Pd-O bond. Figure 4 The XPS spectra of Pd3d and Ce3d of the prepared Pd / CeO2 / SiO2 material can determine the 0 and Pd α+ Coexistence, Ce 3+ The appearance of also indirectly confirms the generation of oxygen vacancies in cerium oxide. Example 2

[0057] Example 1 was repeated, except that the amount of cerium nitrate was changed to 0.04 g, 0.13 g and 0.18 g, to obtain Pd / CeO2 / SiO2 materials with CeO2 / SiO2 mass ratios of 0.05, 0.15 and 0.20, respectively.

[0058] Figure 5 The XRD patterns of Pd / CeO2 / SiO2 materials with different CeO2 / SiO2 mass ratios prepared show that the diffraction peaks are significantly enhanced with the increase of cerium oxide content, which indicates that cerium oxide is loaded on silica, and the absence of Pd diffraction peaks indicates that it is highly dispersed. Figure 6 Raman spectra of Pd / CeO2 / SiO2 materials with different CeO2 / SiO2 mass ratios at 590 cm -1 The peak at 667 cm-1 indicates the presence of oxygen vacancies in cerium oxide. -1 The peak at confirms that Pd interacts with the surface of cerium oxide to form Pd-O bonds; with the increase of cerium oxide content, the number of oxygen vacancies and Pd-O increases significantly. Figure 7 The XPS spectra of Pd3d and Ce3d of Pd / CeO2 / SiO2 materials with different CeO2 / SiO2 mass ratios can be used to determine the Pd 0 and Pd α+ Coexistence, Ce 3+ The appearance of also indirectly confirms the generation of oxygen vacancies in cerium oxide; with the increase of cerium oxide content, the surface Ce 3+ The ratio gradually decreases, indicating that the oxygen vacancy content decreases (Table 1). In addition, the increase in cerium oxide content can facilitate the dispersion of Pd, but it will cover the surface of silicon dioxide, resulting in a decrease in the acid content and specific surface area of ​​the Pd / CeO2 / SiO2 material surface (Table 1).

[0059] Table 1 Surface properties of Pd / CeO2 / SiO2 materials with different CeO2 / SiO2 mass ratios prepared in Examples 1 and 2 of the present invention

[0060]

[0061] Example 3

[0062] Example 1 was repeated, except that the amount of palladium chloride was changed to 0.004 g and 0.016 g, to obtain Pd / CeO2 / SiO2 materials with Pd loadings of 0.5 wt.% and 2.0 wt.%, respectively.

[0063] Comparative Example 1

[0064] 1.0 g hexadecyltrimethylammonium bromide, 4.7 g ethyl orthosilicate and 0.07 g aluminum chloride were weighed and dissolved in 500 mL of a solution with a volume ratio of 4:1 of ethanol to water, and then 20 mL of ammonia water was added to adjust the pH value of the solution to 11.0; the solution was stirred vigorously at 80 °C for 2 hours, and the precipitate was filtered, washed three times with water / ethanol and dried, and then calcined at 550 °C in air to obtain silica; 0.0084 g palladium chloride was dissolved in 1.0 mL of a hydrochloric acid aqueous solution with a pH value of 3.0, and then the palladium chloride solution was added dropwise to 0.51 g silica and stirred for 12 hours; finally, the solution was calcined at 450 °C in air and reduced with hydrogen at 150 °C for 1 hour to obtain Pd / SiO2.

[0065] The element determination results showed that the Pd loading in the prepared Pd / SiO2 material was 1.0 wt.%.

[0066] Comparative Example 2

[0067] 1.0 g of cerium nitrate was dissolved in 5.0 mL of water. Under vigorous stirring, 2.0 mol / L NaOH solution was added to adjust the pH value to 10.5. After filtration and washing, solid cerium hydroxide was obtained. 0.0084 g of palladium chloride was dissolved in 1.0 mL of hydrochloric acid aqueous solution with a pH value of 3.0. The palladium chloride solution was then added dropwise to the solid cerium hydroxide and stirred at 100 °C until the water was completely evaporated. Finally, Pd / CeO2 was obtained by calcining at 450 °C in air and reducing with hydrogen at 150 °C for 1 hour.

[0068] The element determination results showed that the Pd loading in the prepared Pd / CeO2 material was 1.0 wt.%.

[0069] Catalytic effect test

[0070] The Pd / CeO2 / SiO2 material with a controllable hierarchical catalytic structure prepared in Examples 1 and 2 was used to catalyze the furfural hydrogenation reaction. Water was used as the solvent, the hydrogen pressure was 2.0 MPa, and the reaction was carried out at 150 °C for 1 hour. The experimental results are shown in FIG. Figure 8 The furfural conversion rate gradually decreases with the increase of cerium oxide content in Pd / CeO2 / SiO2, while the selectivity of the target product cyclopentanone (CPO) shows a trend of increasing first and then decreasing, and the highest value is when the CeO2 / SiO2 mass ratio is 0.1. The catalytic performance of furfural hydrogenation of Pd / CeO2 / SiO2 material with a CeO2 / SiO2 mass ratio of 0.1 changes with temperature and reaction time. Fig. 9. As the reaction temperature increased from 130 °C to 150 °C, the furfural conversion rate and cyclopentanone selectivity increased significantly; when the reaction temperature was 160 °C, tetrahydrofurfuryl alcohol (THFAL) and other by-products (Others) were significantly generated, so 150 °C was the optimal reaction temperature. The furfural conversion rate and cyclopentanone selectivity increased significantly with the reaction time. After 3 hours of reaction, the furfural conversion rate reached 93% and the cyclopentanone selectivity reached 84%. Fig.10 As shown, after cycle 5, the catalytic performance of the Pd / CeO2 / SiO2 material with a CeO2 / SiO2 mass ratio of 0.1 did not decrease significantly.

[0071] The Pd / CeO2 / SiO2 material with a controllable hierarchical catalytic structure prepared in Examples 1 and 3 above was used to catalyze the furfural hydrogenation conversion reaction. With water as the solvent, the hydrogen pressure was 2.0 MPa, and the reaction was carried out at 150 °C for 1 hour. The experimental results are shown in Table 2. It can be seen that as the Pd loading in Pd / CeO2 / SiO2 increases, the furfural conversion first increases significantly and then tends to be flat; at the same time, too high a Pd loading will significantly reduce the selectivity of cyclopentanone, which may be because the formation of large particles of Pd is conducive to the hydrogenation of the furan ring of furfural to produce tetrahydrofurfuryl alcohol. Therefore, a Pd loading of 1.0 wt.% is the optimal value.

[0072] Table 2 Catalytic performance of Pd / CeO2 / SiO2 materials with different Pd loadings prepared in Examples 1 and 3 of the present invention

[0073]

[0074] The Pd / SiO2 and Pd / CeO2 materials prepared in Comparative Examples 1 and 2 were used to catalyze the hydrogenation reaction of furfural. Water was used as the solvent, the hydrogen pressure was 2.0 MPa, and the reaction was carried out at 150 °C for 1 hour. The experimental results are shown in Table 3. It can be seen that although Pd / SiO2 showed high catalytic activity, the selectivity for cyclopentanone was poor. The furfural conversion rate on Pd / CeO2 was low, but it showed high selectivity for furfuryl alcohol (FAL). The low cyclopentanone selectivity was attributed to the lack of acidity on the cerium oxide surface, which hindered the conversion of furan ring reforming catalyzed by furfuryl alcohol acid to cyclopentanone.

[0075] Table 3 Reaction performance of Pd / SiO2 and Pd / CeO2 materials prepared in Comparative Examples 1 and 2 of the present invention

[0076]

[0077] In summary, the present invention provides a composite material Pd / CeO2 / SiO2 with a controllable hierarchical catalytic structure of Pd, cerium oxide, and silicon dioxide, which realizes the organic combination of the properties of CeO2 and SiO2, thereby efficiently catalyzing the hydrogenation conversion of furfural. The catalyst of the present invention has a simple preparation method, is green and environmentally friendly, has high activity, and has good prospects for industrial application.

[0078] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a composite material of Pd, cerium oxide and silicon dioxide with a controllable hierarchical catalytic structure, characterized in that: The controllable hierarchical catalytic structure Pd, cerium oxide, silicon dioxide composite material is Pd / CeO2 / SiO2; the Pd loading in the composite material is 0.4-2.0 wt.%; and the mass ratio of CeO2 to SiO2 is 0.05-0.20; The preparation method comprises the following steps: Dissolve hexadecyltrimethylammonium bromide, tetraethyl orthosilicate and aluminum chloride in an ethanol aqueous solution, adjust the solution pH to alkaline, stir vigorously, wash and dry the precipitate, and then calcine in air to obtain acidic silica with high specific surface area; dissolve palladium chloride in a hydrochloric acid aqueous solution, then drop the palladium chloride solution onto solid cerium hydroxide, stir until water is completely evaporated to obtain Pd / Ce(OH)4 solid; then, disperse the Pd / Ce(OH)4 solid and acidic silica with high specific surface area in ethanol, stir until ethanol is completely evaporated to obtain a Pd / CeO2 / SiO2 precursor; calcine the Pd / CeO2 / SiO2 precursor in air, and obtain Pd / CeO2 / SiO2 after hydrogen reduction.

2. The preparation method according to claim 1, characterized in that: In air atmosphere, the calcination time of Pd / CeO2 / SiO2 precursor is 3-5 hours, and the heating rate is 1.5℃ / min.

3. The preparation method according to claim 1, characterized in that: The reduction temperature range of the Pd / CeO2 / SiO2 precursor is 150-200°C, and the time is 1-3 hours.

4. The preparation method according to claim 1, characterized in that: The preparation method of the cerium hydroxide solid is as follows: dissolving cerium nitrate in water, adding NaOH solution to adjust the pH value to 10.5 under vigorous stirring; and obtaining the cerium hydroxide solid after filtering and washing.

5. The preparation method according to claim 1, characterized in that: The pH value of the solution is adjusted to be alkaline by using aqueous ammonia to adjust the pH value of the solution to 11.

0.

6. The preparation method according to claim 1, characterized in that: The calcination temperature of Pd / CeO2 / SiO2 precursor in air is 450℃.

7. The preparation method according to claim 1, characterized in that: After washing and drying the precipitate, it is calcined at 550°C in air to obtain acidic silica with a high specific surface area.

8. Use of a composite material of Pd, cerium oxide and silicon dioxide with a controllable hierarchical catalytic structure prepared according to the method according to any one of claims 1 to 7 in the preparation of cyclopentanone by hydrogenation of furfural.

9. The use according to claim 8, characterized in that The furfural hydrogenation conversion time is 0.5-5 hours, and the reaction temperature is 130-150 ° C.

Citation Information

Cited By

  • Preparation method of PdAg nano sponge and application of PdAg nano sponge

    CN117463327A

  • Preparation method of PdAg nanosponge and application of the PdAg nanosponge

    CN117463327B